ANALISIS CIRI KEBAHASAAN DAN EJAAN TEKS EKSPLANASI SISWA KELAS XI SMA NEGERI 1 PAYAKUMBUH TAHUN AJARAN 2018 - Fitri, Indah Rahma; Zulfikarni, Zulfikarni (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
AbstractÂ The purpose of this study was to describe the language and spelling characteristics in the explanatory text of class XI students of SMA 1 Payakumbuh. This type of research is qualitative research with descriptive methods. Data collection is done through documentation studies. The subjects in this study were class XI students of SMA 1 Payakumbuh. The stage of analyzing the data in this study is as follows. First, identify common elements of data. Second, identifying data based on the theory that is a reference. Data identification is done by making a format for identifying linguistic characteristics and explanatory text spelling. Third, analyze data. Fourth, interpret the data that has been analyzed. Fifth, conclude the results of the data description by writing a report. The results of this study are that there are 22 students who have not used the language characteristics of the explanatory text and 8 students have used the explanatory text language characteristics. The linguistic characteristics found in this study are 3, namely, information on time, chronological conjunction and causality conjunction. The time was found as many as 53 pieces, 15 chronological conjunctions and 54 causality conjunctions. In addition, many found errors in the use of spelling in the form of capital letters, periods and commas. The error of using capital letters has 28 errors, 15 misuse of the dot and 158 errors in the use of commas from 810 sentences and 178 paragraphs.Â Kata kunci : Ciri Kebahasaan, Ejaan, Teks Eksplanasi